Neuroprótesis en Otorrinolaringología: más allá del implante coclear. - Alzérreca A., Eugenio; Pardo J., Javiera; Délano R., Paul H. (Revista Hospital Clínico Universidad de Chile, 2011)
Neuroprosthesis or brain-machine interfaces are electronic devices created to directly interact with the nervous system for replacing an absent or damaged sensory or motor function. Three types of auditory neuroprosthetics devices have been developed in Otolaryngology, (i) cochlear implants, (ii) brainstem auditory implants and (iii) auditory midbrain implants. These devices allow young deaf children to acquire oral language and to restore auditory function in deafened adults. On the other hand, a new vestibular prosthesis that could be useful for patients with severe disequilibrium has been developed. Main characteristics and clinical utility of these prostheses are reviewed in this article.